Taxonomic study of Central Asian species of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha: Cicadellidae: Macropsinae). III: Descriptions of two new willow-dwelling species, new synonym, annotated check-list, and key to species - Tishechkin, Dmitri Yu. (Zootaxa, 2015)
Macropsis milkoi Tishetshkin sp. n. from West Tien Shan, Alay and Hissar-Darvaz Mts. (Kyrgyzstan and Tajikistan) and Macropsis anufrievi Tishetshkin sp. n. from Hissar-Darvaz Mts. (Tajikistan) are described. M. elaeagni Emelyanov, 1964 = M. cyanescens Dubovskiy, 1966 syn. n. is redescribed and illustrated based on the material from Central Asia. Annotated check list and key to 30 Macropsis species from Uzbekistan, Kyrgyzstan, Tajikistan and the mountains of Southern Kazakhstan are given.